تأثير الطرق الترابية غير المعبدة على تدهور التربة وتلوث المياه السطحية في المناطق شبه الحضرية (Comprehensive Journal of Science, 2025)
This study evaluates the impact of unpaved dirt roads on soil degradation and surface water pollution in semi-urban areas. The absence of proper engineering design for these roads exacerbates soil erosion during rainy periods and facilitates the transfer of pollutants and sediments into nearby water bodies. The research was conducted in a semi-urban region in western Libya, utilizing field measurements and laboratory analyses of soil and surface water samples. Findings revealed a significant increase in total suspended solids (TSS) in waters adjacent to dirt roads, alongside a decline in soil quality indicators, particularly in terms of bulk density and organic matter loss. Consequently, the study recommends improving road infrastructure through paving or soil stabilization, and implementing effective drainage systems to mitigate polluted runoff